EDUKASI TERAPI REBUSAN DAUN SELEDRI DAN JUS MENTIMUN UNTUK MENURUNKAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS SIGALINGGING KABUPATEN DAIRI - Heriaty Berutu; Rugun Togianur Lingga; Herlina Evi Yanti Manik (Jurnal Abdimas Bina Bangsa, 2024)
WHO states the limit of blood pressure is 120-140 mmHg and systole pressure 80-90 mmHg. This hypertensive disease is often found in developed communities, both men and women, young and old and the symptoms are not clearly visible. These diseases are referred to as silent diseases and are a major risk factor for the development or cause of heart and stoke disease. When not controlled it will cause damage to other organs, such as the brain, kidneys, and eyes and paralysis of the organs of motion. The purpose of this activity is to educate patients giving celery leaf decoction and cucumber juice therapy to lower blood pressure. The service method uses counseling methods using booklets and simulations The target audience in this activity is people with hypertension in the working area of the Sigalingging Health Center, Parbuluan District, Dairi Regency. The resulting output is in the form of a booklet on the therapy of celery leaf decoction and cucumber juice to lower blood pressure in patients with hypertension. Conclusion with the media booklet and simulation of patients with hypertension, it is easier to know and understand about the therapy of celery leaf decoction and cucumber juice to lower blood pressure in patients with hypertension